Improved The Behavior Of The Prevention Of Recurrence Of Hypertension On The Elderly Through Empowerment Support Group - Rina Nur Hidayati; Faisal ibnu; Ifa Roifah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Hypertension in the elderly can actually be prevented, but the lack of adequate knowledge about the elderly hypertension and prevention efforts are likely to increase the number of occurrence of hypertension and hypertension occurred so often repeated (relapse). With empowerment Support Group is expected to be an increase in prevention of recurrence behavior of hypertension in the elderly. The purpose of the study is to know the influence of the support group against the behavior of the elderly in the prevention of recurrence of hypertension at the village and subdistrict Bicak Trowulan Mojokerto. The design used was pre experiments with one group pre test and post testdesign. This research sample 24 elderly by using purposive sampling technique. Data collection through the pre test and post test using a questionnaire about the behavior of the elderly in the prevention of recurrence of hypertension. Intervention support group provided for 8 weeks. Data processing is started from the editing, coding, scoring and tabulating. then conducted a test of a different mode. The results showed there was a positive change in behavior in the prevention of recurrence of hypertensive elderly in the village of Trowulan subdistrict of Mojokerto Bicak. Empowerment Support group is effective in improving the behavior of the elderly in the prevention of recurrence of hypertensive diDesa Bicak subdistrict of Mojokerto Trowulan as much as 83.4%, because of the support group is a group that teaches the assistance and guiding the elderly behave healthy life which will result in reducing or eliminating personal and social problems.